A multi-scale perspective on ant diversity in semiarid landscapes - Bestelmeyer, Brandon Thomas, author; Wiens, John A., advisor; Herbers, Joan, committee member; Kondratieff, Boris C., committee member; Lauenroth, W. K., committee member (Colorado State University. Libraries, 2000)
Documenting biodiversity patterns and understanding the multiscale processes that create them is an important front of progress in both landscape ecology and conservation biology. One problem in understanding such patterns centers on the differences between how landscapes are perceived by investigators and land managers on the one hand, and the variety of organisms that they are trying to manage, on the other. Are these perceptions concordant? I address this question and related issues by examining the correlates of variation in ant diversity, species composition, and their contributions to the redistribution of scavenged materials with respect to 1) habitat variation defined by ecologists according to grazing management and natural shifts in vegetation within 100-km2 landscapes at three Long-Term Ecological Research (LTER) sites, and 2) a biome transition from the shortgrass steppe to the Chihuahuan desert grassland biome that is represented by changes in dominant vegetation at the LTER sites. I also considered ant community variation at fine scales with respect to shrub microhabitats in a landscape dominated by Sonoran thomscrub. Grazing was the dominant land use in the LTER landscapes, and had large effects on vegetation. Despite this, ant communities and scavenging patterns were relatively little affected by grazing. Instead, soil characteristics were shown to be the most consistent correlate of ant composition at the LTER sites. Vegetation contrasts between grasslands and shrublands sometimes paralleled soil contrasts, and sometimes did not. Some ant species were associated directly with particular plants that defined vegetation types, and some others could be linked to particular soil textural characteristics. Across the biome transition, ant composition and the representation of ant faunal complexes changed, but not in step with vegetation. Contrary to predictions, ant diversity was not greatest at the vegetation-defined biome transition. Overall, ants responded to variation in soils and climate in ways that were distinct from those of vegetation. These results support the notion that patterns from several, functionally-distinct focal taxa will be required to characterize landscape species diversity adequately. Existing techniques that rely on vegetation pattern to characterize landscapes may be limited in their capacity to represent habitat variation for some taxa.
Keywords: ecology; entomology